Democracia, desigualdades e direitos desterritorializados: um esboço da questão - José Rogério Lopes; José Luiz Bica de Mélo (Ciências Sociais Unisinos)
The present article analyses the contemporary process of expression of inequalities and its challenges for democracy and for the sociological analysis, considering a scenario of contingencies defined into new ways of stratification and social conflicts, or degrees of perception and solution of collective demands. Such scenario is shaped in correspondence to the method of space analysis by Milton Santos, and for this particular work we have adopted the principle that says that the processes of spatial, economical and social transformation, especially in the last decades, gave way to a complex and deterritorialized arena of constructions and fight for rights.